Creating Spatial Synergies around Food in Cities. Issue 1 (23rd February 2017) - Koopmans, Marlinde E.; Mettepenningen, Evy; Kunda, Ilona; Keech, Daniel; Tisenkopfs, Talis
Abstract : This paper focuses on the phenomenon of multifunctional urban food initiatives (MUFIs) and how, using food as a vehicle, they provide integrative solutions for a number of social, environmental and economic problems in European cities. Through an in‐depth investigation of three MUFIs in the UK, Latvia, and Belgium, the paper aims to increase understanding on how different activities are combined within MUFIs, leading to the creation and strengthening of synergies: both internal, between the different activities performed within MUFIs, and external synergies between the MUFI and the (peri‐)urban environment in which it operates. The three cases illustrate that the dense and complex urban environment in which they are situated provides possibilities to create a wide, diverse network around food, leading to a high potential for synergies to occur. In this way, MUFIs can respond to specific urban needs, which are not addressed by the state, and therefore have an important signaling function. For the MUFIs themselves, although being multifunctional increases opportunities, it is also a challenge to find the right balance between the different functions and not to lose sight of the economic side of the business. Local governments can support MUFIs by providing space for them, room to experiment, adapting regulations to getting MUFIs out of the "grey zones" of legislation, and by starting to strategically think about food in their city region.